1979
DOI: 10.1073/pnas.76.9.4617
|View full text |Cite
|
Sign up to set email alerts
|

Some sequence similarities among cloned mouse DNA segments that code for lambda and kappa light chains of immunoglobulins.

Abstract: A comparison between the cloned mouse DNA segments that were found to code for the X and K light chains of immunoglobulins established that there were seven short nucleotide sequences, two of which matched 6 out of 7, two 7 out of 8, two 8 out of 9, and one 9 out of 10 bases; these sequences were located either at homologous amino acid positions or at positions displaced by four amino acids or less. They all occurred in the framework regions (FRs), five next to the complementarity-determining regions (CDRs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The consensus analysis was performed in reference to sets of VH and VL consensus sequences defined by Kabat. 50 Each tyrosine residue in the CDR L1, L2, L3 or H2 of the initial scFv was identified and replaced with the amino acid that occurs most frequently in the natural antibody repertoire. Tyrosines that were found in a position more than 90% of the time were not mutated.…”
Section: Tyrosine Scanningmentioning
confidence: 99%
“…The consensus analysis was performed in reference to sets of VH and VL consensus sequences defined by Kabat. 50 Each tyrosine residue in the CDR L1, L2, L3 or H2 of the initial scFv was identified and replaced with the amino acid that occurs most frequently in the natural antibody repertoire. Tyrosines that were found in a position more than 90% of the time were not mutated.…”
Section: Tyrosine Scanningmentioning
confidence: 99%
“…Lines of evidence have clearly shown that the complementarity determining regions (CDRs) are preferred targets of mutation to the framework regions of the Ig V regions, as originally proposed by Wu et al 119) The three-dimensional structure of Ig has established the functional significance of CDR as antigen binding site. Subsequently, extensive studies have been carried out to look for any primary sequences associated with mutation sites, and these revealed a few preferred motifs, among which the RGYW motif is approximately twofold more frequently mutated than by chance.…”
Section: Somatic Hypermutationmentioning
confidence: 94%
“…Databases of VH and VL protein sequences derived from NCBI Entrez Protein database were used to establish the individual amino acid frequencies at each residue position of natural antibody repertoire. The consensus analysis was performed in reference to sets of VH and VL consensus sequences defined by Kabat 47 . Canonical analysis was performed in reference to canonical structural residues critical to CDR conformation 48 .…”
Section: Methodsmentioning
confidence: 99%